Optimizing Sustainable Transportation Policies and Mobility Technologies to Reduce Air Pollution and Traffic Congestion in Jakarta - Bakri Bakri; Khairul Nur Adli (Westscience Press, 2026)
Air pollution and traffic congestion continue to pose significant challenges to sustainable urban development in Jakarta. Rapid population growth, increasing vehicle ownership, and expanding mobility demands have intensified environmental degradation and transportation inefficiencies throughout the metropolitan area. This study aims to analyze the influence of sustainable transportation policies and mobility technologies on reducing air pollution and traffic congestion in Jakarta. A quantitative research approach was employed using data collected from 175 respondents representing public perceptions of urban transportation conditions. Data were gathered through a structured questionnaire utilizing a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings reveal that sustainable transportation policy has a positive and significant effect on air pollution reduction and traffic congestion reduction. Furthermore, mobility technology significantly influences air pollution reduction and demonstrates the strongest effect on traffic congestion reduction. The model explains 66.4% of the variance in air pollution reduction and 70.1% of the variance in traffic congestion reduction, indicating substantial explanatory power. The results suggest that the integration of sustainable transportation policies and smart mobility technologies can effectively improve environmental quality and transportation efficiency in Jakarta. This study contributes to the sustainable urban mobility literature by providing empirical evidence that policy interventions and technological innovations function as complementary mechanisms for addressing complex transportation challenges in rapidly urbanizing cities.